DFT calculations of the redox potentials for the nitrosyl complexes [Fe2(μ‐RS)2(NO)4] with R = alkyl. Issue 5 (19th March 2012) - Emel'yanova, Nina S.; Shestakov, Alexander F.; Sanina, Nataliya A.; Gidopoulos, Nikitas I.; Theophilou, Andreas K.
Abstract The redox potentials of alkyl substituted Roussin's red esters in tetrahydrofuran and acetonitrile were studied using the density functional theory. The geometry and electronic structures of monoanions of Roussin's red esters [Fe2(μ‐RS)2(NO)4]− (R = Me, Et, i‐Pr, t‐Bu) together with their redox potentials in solutions have been computed using GGA (BP86, PBE, BLYP), meta‐GGA (TPSS), hybrid‐GGA (B3LYP), and meta‐hybrid GGA (BMK, B1B95) combined with 6‐311++G**//6‐31G* and tzvp basis set. The BP86 functional provides excellent agreement with experiment, whereas B3LYP requires some correlation, which makes it possible to estimate the redox potentials of related complexes, intermediate, or unstable. In particular, a redox potential of the complex with R = Ph, a perspective anticancer drug, has been evaluated for several solvents. © 2012 Wiley Periodicals, Inc.